Performance improvement of third-party logistics providers ? an integrated approach with a logistics information system. (2nd May 2008) - Liu, John J.; So, Stuart C.K.; Choy, K.L.; Lau, Henry; , S.K. Kwok
Many third-party logistics (3PL) providers in the Pearl River Delta (PRD) region are small to medium companies, which play an important role in outbound logistics, managing logistics activities in the manufacturing supply chain in the Greater China. It is necessary for these companies to improve information transparency to their supply chain partners to maintain competitiveness. In this paper, a logistics information management platform known as Integrated Logistics Information Management System (ILIMS) is presented to suit this need. ILIMS aims to provide 3PL companies a uniform way of doing business with other trading partners and managing operation performance online. Besides, it enables 3PL companies to communicate with different trading partners on the internet without geographical restriction. A case study is presented with the application of ILIMS to a medium-sized 3PL company. With this generic system, the overall outbound logistics performance of the supply chain was significantly improved.